Akuntabilitas dalam Transaksi Keuangan Perspektif Islam: Accountability in Financial Transaction from an Islamic Perspective - Azwar, Azwar (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This research aims to describe the concept of accountability in financial transaction from an Islamic perspective. The study employs a qualitative method with a library research approach. The findings indicate that accountability in financial transactions according to Islamic perspectives encompasses a broader dimension than merely fulfilling social and legal responsibilities as practiced in the modern economic system. The main principles underlying accountability in Islam include honesty, trustworthiness, justice, and transparency, all of which are outlined and emphasized in the Qur'an and Hadith. In the context of modern finance, these principles can be implemented in various ways, including avoiding usury (riba), using fair contracts, paying zakat and charity, and utilizing Sharia-compliant financial institutions and audits. By applying Islamic accountability principles, financial transactions can be conducted more fairly, transparently, and responsibly. This supports the creation of sustainable economic and social welfare, ensuring that every financial transaction not only meets worldly legal standards but also possesses a strong spiritual and moral dimension.